Enamel ribbons, surface nodules, and octacalcium phosphate in C57BL/6 Amelx−/− mice and Amelx+/− lyonization. Issue 6 (5th October 2016) - Hu, Yuanyuan; Smith, Charles E.; Cai, Zhonghou; Donnelly, Lorenza A.‐J.; Yang, Jie; Hu, Jan C.‐C.; Simmer, James P.
Abstract: Background: Amelogenin is required for normal enamel formation and is the most abundant protein in developing enamel. Methods: Amelx +/+, Amelx +/ −, and Amelx − / − molars and incisors from C57BL/6 mice were characterized using RT‐PCR, Western blotting, dissecting and light microscopy, immunohistochemistry (IHC), transmission electron microscopy (TEM), scanning electron microscopy (SEM), backscattered SEM (bSEM), nanohardness testing, and X‐ray diffraction. Results: No amelogenin protein was detected by Western blot analyses of enamel extracts from Amelx − / − mice. Amelx − / − incisor enamel averaged 20.3 ± 3.3  μ m in thickness, or only 1/6th that of the wild type (122.3 ± 7.9  μ m). Amelx − / − incisor enamel nanohardness was 1.6 Gpa, less than half that of wild‐type enamel (3.6 Gpa). Amelx +/ − incisors and molars showed vertical banding patterns unique to each tooth. IHC detected no amelogenin in Amelx − / − enamel and varied levels of amelogenin in Amelx +/ − incisors, which correlated positively with enamel thickness, strongly supporting lyonization as the cause of the variations in enamel thickness. TEM analyses showed characteristic mineral ribbons in Amelx +/+ and Amelx − / − enamel extending from mineralized dentin collagen to the ameloblast. The Amelx − / − enamel ribbons were not well separated by matrix and appeared to fuse together, forming plates. X‐ray diffraction determined that the predominant mineral in Amelx − / − enamel is octacalcium phosphate (not calcium hydroxyapatite). Amelx − / − ameloblasts were similar to wild‐type ameloblasts except no Tomes' processes extended into the thin enamel. Amelx − / − and Amelx +/ − molars both showed calcified nodules on their occlusal surfaces. Histology of D5 and D11 developing molars showed nodules forming during the maturation stage. Conclusion: Amelogenin forms a resorbable matrix that separates and supports, but does not shape early secretory‐stage enamel ribbons. Amelogenin may facilitate the conversion of enamel ribbons into hydroxyapatite by inhibiting the formation of octacalcium phosphate. Amelogenin is necessary for thickening the enamel layer, which helps maintain ribbon organization and development and maintenance of the Tomes' process. Abstract : We thoroughly characterized enamel formation in amelogenin null mice and determined that the mineral covering dentin in these animals is octacalcium phosphate. The initial enamel mineral has a ribbon shape, similar to the wild type. Thus, amelogenin is not required to shape the ribbons, as is currently thought, but is required to ensure that the final mineral phase is calcium hydroxyapatite.